Fuzzy-logic-control of two-switch & three-switch-serial-input interleaved-forward-converters - Lakshmi Ramalingam; K. Karunanithi; P. Chandrasekar (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This manuscript manages F-L-C of “two-switch& three-switch-interleaved-forward- -converters” with DC-engine-load”. Numerous modern applications require DC-power. This forward-converter convert's unregulated DC-capacity to controlled DC-control. It contains high recurrence transformer which is additionally called ‘isolation-transformer’. This gives disconnection among load& fundamental-circuit. The AC- control is amended utilizing half-wave-rectifier. The swell in the yield is separated utilizing pi- filter. FLC is intended for two-switch and three-switch forward-converter-systems. The simulation is completed by utilizing MATLAB-simulink. The controller execution is considered for different estimations of load-torque for both two-switch& three-switch forward-converter -frameworks.